Ultrasound assessment of brain supplying arteries (extracranial) - Gröschel, Klaus; Harrer, Judith U.; Schminke, Ulf; Stegemann, Emilia; Allendörfer, Jens (Ultraschall in der Medizin - European Journal of Ultrasound, 2023)
Ultrasonography of the brain-supplying arteries is a non-invasive and highly efficient technique for the assessment of a stenosis or a vessel occlusion in patients with cerebrovascular diseases. This article reviews the examination technique for a standardized ultrasound assessment of the extracranial carotid and vertebral arteries. It further describes the multiparametric grading criteria of internal carotid artery stenosis and it gives recommendations for a standardised documentation of findings. Additionally, it proposes recommendations for intima-media thickness measurement and for classifying atherosclerotic plaques with B-mode ultrasonography. Moreover, criteria for the diagnosis of in-stent stenoses, vertebral artery dissections and subclavian steal syndrome are provided.Die Sonografie der hirnversorgenden Arterien ist eine nicht invasive und hoch effiziente Technik für die Beurteilung von Stenosen oder eines Gefäßverschlusses bei Patienten mit zerebrovaskulären Erkrankungen. Dieser Artikel fasst die Untersuchungstechnik für eine standardisierte Ultraschallbeurteilung der extrakraniellen Karotis und der A. vertebralis zusammen. Darüber hinaus werden die multiparametrischen Graduierungs-Kriterien für die Karotisstenosen (A. carotis interna) beschrieben und Empfehlungen für eine standardisierte Dokumentation der Befunde gegeben. Zudem werden Empfehlungen für die Messung der Intima-Media-Dicke und für die Klassifizierung atherosklerotischer Plaques mit B-Mode-Ultraschall genannt. Außerdem werden Kriterien für die Diagnostik von In-Stent-Stenosen, Vertebralisdissektionen und des Subclavian-Steal-Syndroms angegeben.